QUALITY STUDY OF DOMESTIC WASTEWATER IN RIVERS PASSING THROUGH MANADO CITY BASED ON ORGANIC AND INORGANIC MATERIALS - Tarigan, Adianse; Lasut, Markus T.; Tilaar, Sandra O. (JURNAL PESISIR DAN LAUT TROPIS, 2013)
Study on the quality of domestic wastewater in rivers passing through Manado City to Manado bay was done based on organic and inorganic materials. The study aimed to provide suitable information for environmental management of rivers and beaches in the city. Three rivers were selected to be observed, such as S. Bailang, S. Maasing and S. Tondano, using parameter of Biological Oxygen Demand-5 days (BOD5), Phosphate (PO4) and Nitrate (NO3). Water samples were taken from three locations (upper, middle and river mouth parts) in each rivers. The result showed that average concentrations of the parameters, respectively, were 2 mg/L, 0.014 mg/L and 0.388 mg/L in S. Bailang; 17.66 mg/L, 1.858 mg/L and 0.029 mg/L in S. Maasing; and 4 mg/L, 0.289 mg/L and 0.314 mg/L in S. Tondano. In this paper, water quality status of the observed rivers based on current regulation was discussed.